2015 Chinese Automation Congress (CAC) 2015
DOI: 10.1109/cac.2015.7382502
|View full text |Cite
|
Sign up to set email alerts
|

Composite learning control with application to inverted pendulums

Abstract: Composite adaptive control (CAC) that integrates direct and indirect adaptive control techniques can achieve smaller tracking errors and faster parameter convergence compared with direct and indirect adaptive control techniques. However, the condition of persistent excitation (PE) still has to be satisfied to guarantee parameter convergence in CAC. This paper proposes a novel model reference composite learning control (MRCLC) strategy for a class of affine nonlinear systems with parametric uncertainties to gua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 34 publications
(31 reference statements)
0
13
0
Order By: Relevance
“…The first proposed relaxation method and those in other works [24][25][26][27][28][29] store information via integration. The second method uses delay, which is more close to concurrent learning [20][21][22][23] with direct using of the previous measurements in the estimator.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first proposed relaxation method and those in other works [24][25][26][27][28][29] store information via integration. The second method uses delay, which is more close to concurrent learning [20][21][22][23] with direct using of the previous measurements in the estimator.…”
Section: Resultsmentioning
confidence: 99%
“…Another method is called composite learning, which is proposed in the work of Pan et al 24 and developed in other works of Pan et al 25,26 This method also utilizes both current and online recorded data. However, there are not the history stack and measurements selecting algorithm.…”
mentioning
confidence: 99%
“…Simulation results have shown that the proposed approach possesses superior control performances under both noise‐free and noisy‐measurement environments. Further work would focus on composite learning control using online recorded data .…”
Section: Discussionmentioning
confidence: 99%
“…Define the vector Y e and the matrix M e as given in (7). Consider the estimator (11) with φ and Y i defined in (10) and 9, respectively. The implication (13) holds.…”
Section: B Proposed Dynamic Regressor Extension and Mixing Proceduresmentioning
confidence: 99%